Penerapan Peraturan Daerah Kabupaten Maluku Tengah Nomor 11 Tahun 2022 Tentang Pengelolaan Sampah Di Wilayah Pesisir Kecamatan Kota Masohi Kabupaten Maluku Tengah - Samal, Hikma Fajaria; Sedubun, Victor Juzuf; Irham, Muhammad (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2023)
Environmental health in Indonesia is still a very diverse problem and from year to year it has not been resolved properly. Problems that occur include pollution problems, both water pollution, air pollution, and soil pollution. The writing method in this study uses an empirical juridical method with a statute approach. The data sources used are primary data sources in the form of interviews and observations and secondary data in the form of journals, books and data on the internet related to research. Data was collected through observation, interviews and documentation. The results of the study show that (1) waste management in the coastal area of ​​Kota Masohi District is not running according to regulations, as seen from the lack of attention from the government and the untouchability of infrastructure and services for waste management in the area. (2) the community's role was not carried out properly due to a lack of understanding of the regional regulation and the government did not carry out its role properly due to budget constraints. The implications of the research are (1) It is hoped that the government will be more active in disseminating the Central Maluku Regency Regional Regulation No. 11 of 2022 concerning Waste Management sees that many people do not know the contents of the regional regulation (2) It is hoped that the Environmental Service can carry out their duties and functions in implementing the regional regulation. (3) It is expected that the community will always play an active role in assisting the government in maintaining environmental cleanliness and health.